Administration, Monitoring and Analysis of Supercomputers in Russia: a Survey of 10 HPC Centers - Voevodin, Vadim V.; Chulkevich, Roman A.; Kostenetskiy, Pavel S.; Kozyrev, Vyacheslav I.; Maliutin, Anton K.; Nikitenko, Dmitry A.; Rykovanov, Sergey G.; Shamsutdinov, Artemiy B.; Shkandybin, Yurii N.; Zhumatiy, Sergey A. (Supercomputing Frontiers and Innovations, 2021)
Supercomputer technologies are in demand for solving many important and computationallyintensive tasks in various fields of science and technology. Therefore, it is not surprising that there are several dozen supercomputer centers only in Russia. However, the goals of creating such centers, as well as the range of tasks solved in them, can vary greatly, therefore the structure of supercomputers and the policies for their usage can significantly differ. This leads to the fact that many supercomputer centers live an isolated life – the administrators of such centers tend to solve administration-related tasks on their own, despite the fact that solutions for many similar tasks have already been developed and applied in other centers. This can happen due to different reasons, but in any case, this situation could and should be improved. To do this, it is worth establishing a closer connection between supercomputer centers, which will allow more actively exchanging experience or jointly developing desired system software. In order to understand the current situation in this area, a survey was conducted of representatives among 10 large supercomputer centers in Russia, and its results are presented in this paper. Two relevant topics about using monitoring data in practice and real-life examples of supercomputer functioning improvement are also discussed here in more detail. Their vision on these topics is provided by the system administrators of HSE University, Skoltech and Moscow State University.